Comprehending microplastic pollution in diverse environment: Assessing fate, impacts, and remediation approaches - Yadav P.; Mishra V. (My University, 2025)
Microplastics (MPs) pose pervasive environmental threats that potentially harm ecosystems and public health. Till date, most of the researches have predominantly concentrated on freshwater and marine ecosystems. This review attempts to provide current knowledge of microplastic pollution, its source, and its fate in all environmental compartments for instance soil, water, and atmosphere. Also briefly summarizes different MP's exposure routes and their negative consequences on public health. Various conventional methods have been used to remove MPs but these are inefficient owing to several demerits. Microbial approach is regarded as a safer option for removing MPs due to its unique metabolic mechanism. More than 400 microorganisms have been discovered as capable of MPs degradation. Fungi have appeared as the most proficient degraders of plastics among the microbes because they release unique enzymes and can thrive on hazardous components with low resources. Numerous fungal species that can break down various plastic kinds have been found in recent studies; nevertheless, there are still many unanswered questions regarding the mechanisms underlying biodegradation. The molecular mechanisms behind MP degradation via various enzymes have received little attention. Also, white-rot fungi have received the least attention among the fungi examined for biodegradation despite having a unique extracellular enzymatic system. Thus, the current study summarizes the ability of fungi that degrade various polymers and the function of multiple enzymes in the degradation of MPs. Also, the role of different extracellular and intracellular enzymes in biological degradation of MPs is discussed. Prospects for the future include tracking long-term trends in microplastic contamination, evaluating the effectiveness of clean-up techniques, and integrating the developed technologies with socioeconomic factors into policy frameworks. © 2024 Elsevier Ltd